Late-Holocene drought and fire drove a widespread change in forest community composition in eastern North America. (July 2015) - Clifford, Michael J; Booth, Robert K
Several regions of the world have recently experienced climate-induced changes in forest composition, highlighting the need to understand the causes, likelihood, and dynamics of abrupt vegetation change. Although few historical examples of climate-induced forest change exist from recent centuries, particularly in humid regions like the northeastern United States, paleoecological records are rich with examples. For example, pollen records from portions of the northeastern United States indicate that eastern hemlock ( Tsuga canadensis ) and American beech ( Fagus grandifolia ) abruptly declined in abundance between 500 and 600 yr BP. Concomitant increases in pine ( Pinus spp.) and oak ( Quercus spp.) occurred. Hypotheses to explain this change have included cooling during the 'Little Ice Age' (LIA), Native American activity, drought, and/or fires. To better understand spatiotemporal patterns of forest change and assess potential causes and dynamics, we synthesized regional pollen records and developed two high-resolution, coupled records of vegetation, fire, and drought from bogs in Maine. Results of our synthesis reveal >70% of regional pollen sites recorded shifts in forest composition during this time period. Bog records revealed that forest composition changed a few decades after the onset of drought and regional fires, consistent with increased recruitment of pine and oak during post-disturbance succession. Vegetation changes persisted until European settlement. Our data demonstrate that widespread, long-lasting forest changes were triggered by decadal-to-multidecadal drought and associated fires, highlighting the potential for abrupt, long-lasting forest changes in response to transient climate and disturbance events, particularly when such events occur against the backdrop of more gradual temperature change.